Experimental validation of a multi-material acoustic black hole - Anil Bastola (The Journal of the Acoustical Society of America, 2023)
Geometric acoustic black holes (ABHs) have already been proven as an effective passive vibration control measure in plates and beams. However, the thin geometries inherent to the design raise concerns about the structure’s resistance to damage through fatigue. Multi-material ABHs (MM-ABHs) have been proposed as an alternative solution where by the material properties vary along the direction of wave propagation instead of the geometry. This, in theory, produces a change in acoustic impedance without the issues of fatigue seen in the geometric ABHs. Previous work has been performed on the design and modeling of polymer multi-material ABHs. This work discusses practices for experimental measurement and validation of multi-material ABHs produced through additive manufacturing.